Facilitating the subject of emergency management in forest research - Ha, Kyoo-Man (Frontiers in Forests and Global Change, 2025)
This brief perspective served as a facilitator to emergency management for the benefit of forest research. While maintaining the relative (or more restrictive) criteria of emergency management domain, a systematic literature review was adopted as a main methodology. While current forest research made headway in adjusting to changing environmental conditions such as fire management, there was still room for improvement. In particular to further make forests resilient and sustainable, future forest research as key findings should incorporate multiple principles of emergency management (including comprehensive emergency management, other emergency management frameworks, prospective research areas, pertinent research questions, communication, etc.). Then, future forest research should apply them to its projects based on potential benefits (including both expanding research opportunities and contributing to the goal of emergency management). This perspective further introduced emergency management, which would help to expand the scope of forest research.